Residência Pedagógica E Formação De Professores Em Alagoas: Vivências E Reflexões Sobre O Ensino De Língua Espanhola (PERcursos Linguísticos, 2021)
This paper aims to present some reflections regarding a study carried out in the Spanish Residência Pedagógica Program, especially regarding the continuing education of two mentor teachers participanting in the program. Theoretically, we were underpinned on teacher education (NÓVOA, 1995; DELORS, 2013; MARQUES; PIMENTA, 2015) and on the perspective of critical literacy (DUBOC, 2016; MOTTA, 2008; JANKS, 2016).  In this investigation, we seek to highlight the need for education and motivation of the teachers in relation to the construction of new knowledge, supported by the development of criticality, relfecton and transformation of situated pedagogical practices. The data collection instruments of the qualitative research were interviews with the mentors and reports form the resident students. As a result, we found that the Spanish Residência Pedagógica provided mentor teachers with the the possibility to reflect on the importance of continuing education, to (re) think about their practices and to reconstruct them.Keywords: Pedagogical Residency Program. Teacher training. Critical literacy. Spanish language.